Circular Economy of Tourism in Delhi - Singh, Sheo Pratap; Sajnani, Manohar; Arora, G. K. (Prabandhan: Indian Journal of Management, 2023)
The global biodiversity loss and CO2 emissions are primarily attributed to the increasing use of natural resources and the existing â€œtake-make-wasteâ€ development process. Such practices conflicted with the globally agreed sustainability moves toward achieving sustainable development goals, pollution mitigation missions, and green greenhouse gas emissions. Hence, the circular economy model was becoming widely popular. Tourism is indisputably the leading industry and has suffered heavily due to the COVID-19 pandemic. There was an opportunity to rebuild safe, equitable, sustainable, and climate-friendly tourism. This study utilized Delhi as a case study to investigate the relationship between circulatory economic systems and travel and tourism. In 2021, 6.1 lakh foreign tourists went through Delhi, the capital of India, which is home to three World Heritage Sites and functions as a center for international crossings. Delhi is unquestionably a fascinating travel destination, but it also has a serious pollution issue, which poses a major â€œurban challengeâ€ and has a huge â€œcongestion cost.â€ Thus, there are a plethora of opportunities to implement a circular economy within the tourism industry. This study examined the wide range of actions and policies implemented by the State Government to encourage sustainable tourism and raise the standard of living for both residents and tourists. This study showed that Delhiâ€™s tourism industry has a lot of room for the circular economy and that even with the State Governmentâ€™s many initiatives, much work needs to be done to improve the ecosystem and its managerial capacity. The main goals should be the separation of hazardous products, water, food, and electronics waste, and the implementation of energy-efficient technology.